Archipelagic Administration Public Service in Central Maluku - Normawati Normawati; Hengky V. R. Pattimukay; Humairah Almahdali (Universitas Padjadjaran, 2024)
The focus of this research is the issue of public service administration of the islands in Central Maluku Central is less proficient in complying with the demands and requirements of the public for efficient and effective public service. Moreover, the main problem for the community is the operational costs, transportation, and accommodation required to access public services. To date, there has been no effective policy or action by the local government to shorten the range of controls. It will be a strategic step in the administration of the islands to provide a public service that meets the needs and demands of the community of Central Maluku Regency. The purpose of this study is to explain how public service is in the administration of Central Maluku and to identify the aspects that affect it. Considering policy elements, scope of control, operationalization, responsibility, and quality, its conceptual approach is based on real problems and situations. The research involved 105 samples, and quantitative analysis was done using a frequency table. The results of the analysis are expected to produce a clear and relevant sociogram on the development and improvement of public services in the administration of the islands in the Central Maluku Regency. This research is also expected to provide empirical evidence that is beneficial for the advancement of science and improving the quality of public service in the region.